Absence Epilepsy and Moyamoya Disease - J Gordon Millichap (Pediatric Neurology Briefs)
The case of a 6-year-old girl with typical absence epilepsy associated with moyamoya disease (MMD) is reported from the Department of Neurosurgery, Kyoto University Graduate School of Medicine, Japan.